ASEAN Intergovernmental Commission on Human Rights (AICHR) as Limited Norm Localization in Rohingya Human Rights Protection - Ridani, Syahri; Sundrijo, Dwi Ardhanariswari (Review of International Relations, 2025)
This study analyzes how the ASEAN Intergovernmental Commission on Human Rights (AICHR) functions as an outcome of limited norm localization in the protection of human rights for the Rohingya ethnic group. Employing Acharya’s (2004) norm localization theory, the study traces the process of adapting global human rights norms into the ASEAN framework, which faces challenges due to the principles of non-interference and state sovereignty among member countries. The findings reveal that although AICHR was established to promote and protect human rights, it faces structural and functional limitations. its consultative mandate, absence of investigative mechanisms, and the dominance of the ASEAN Way, particularly consensus and non-intervention, render AICHR ineffective in responding to the Rohingya crisis. Analysis through the four stages of localization (contestation, local initiative, adaptation, and amplification) indicates that AICHR functions more as a symbolic commitment to human rights within ASEAN rather than as a genuine protective mechanism. The study concludes that without mandate reform and adjustments to ASEAN principles, AICHR will continue to fall short in addressing systematic human rights violations such as those experienced by the Rohingya. This implies the need for a redefinition of global human rights norms that are more contextually grounded in regional values